Hubungan Lama Beternak dan Jumlah Ternak dengan Tingkat Adopsi Inovasi Pakan Awetan pada Peternak Kambing di Kecamatan Cilongok Kabupaten Banyumas - Nulhak, Junjunan Insan; Muatip, Krismiwati; Hidayat, Nur (ANGON: Journal of Animal Science and Technology, 2021)
Background. This research, with the title of the relationship between the length of time and the number of livestock and the adoption rate of preserved feed innovation, was carried out on 12 November to 11 December 2020 in Cilongok District, Banyumas Regency. This study aims to determine the length of time to raise goats, the number of goats raised, the adoption rate of preserved feed innovation, and to analyze the relationship between the length of raising and the number of livestock with the adoption rate of preserved feed innovation in Cilongok District. Materials and methods. The method used in this research is a survey method, the determination of the sample area is done by purposive sampling, namely Cilongok District which has a fairly high goat population. Cilongok sub-district has 20 villages, of which 15% were taken as a sample village. The village sample was selected by purposive sampling, namely villages that had a population of breeders and goats, namely Cikidang Village, Batuanten Village and Gunung Lurah Village. Determination of the number of respondents using the Slovin formula. Sampling was done by random sampling as many as 63 breeders. The analytical method used is descriptive analysis and Spearman rank correlation analysis. Results. The results showed that the goat breeders in Cilongok Subdistrict, Banyumas Regency, had a long time to breed and the number of livestock was in the medium category. Goat breeders in Cilongok District are aware of the preserved feed technology (silage) but only 17.46% have tried making preserved feed and no one has adopted this innovation.